Analisis Program Pemberian Makanan Tambahan (PMT) Dalam Menanggulangi Stunting Perspektif Maqashid Syariah di Desa Suci Kecamatan Panti Kabupaten Jember - Alfatia Safitri; Sofiah Sofiah (CV. ITTC INDONESIA, 2025)
This study aims to analyze the implementation of the Supplementary Feeding Program (PMT) in addressing stunting from the perspective of Maqasid Syariah in Suci Village, Panti District, Jember Regency. This research employs a descriptive qualitative method with a field research approach. Data were collected through observation, interviews, and documentation, and then analyzed qualitatively. The findings reveal that: (1) The implementation of the PMT program in tackling stunting in Suci Village has been carried out systematically during the planning, preparation, and implementation stages. However, the recording and reporting stages have not yet been fully aligned with the established standards. (2) The PMT program in Suci Village aligns with the five principles of Maqasid Syariah, particularly in the economic aspect. The program contributes to the preservation of wealth (hifdz al-mal) by alleviating the economic burden on families.